FACTORS AFFECTING THE DECISION TO USE CLOUD STORAGE SERVICES - Supaporn, Pitiphak; Visitnitikija, Chinnaso (Journal of MCU Nakhondhat, 2024)
A study of marketing mix factors affecting the decision to use cloud service aims to 1) The marketing mix factors influencing the use of cloud services. 2) The comparison of decision-making processes in using cloud services based on personal demographic data. A sample group of 400 respondents was selected, with a questionnaire used as the research instrument. The data were analyzed using statistical methods, including percentage, mean, t-test, F-test (One-way ANOVA), and Multiple Regression Analysis. The results indicated that most respondents were male, aged between 31 - 40 years, held a bachelor's degree, worked for private companies, and had an average monthly income of 20,001 - 40,000 THB. Both the marketing mix factors and the comparison of decision-making processes in using cloud services were found to be of high importance, with service security and technology being the most critical factors. It was found that gender, age, education level, and monthly income had a statistically significant influence on the decision to use cloud services at the 0.05 level. Product, price, promotion, and physical evidence also had a statistically significant impact on decision-making at the 0.05 level. Regarding security, cloud services must have hyper-infrastructure and tools to identify system access, with information security management standards significantly influencing the decision at the 0.05 level. In terms of technology, the system must support all forms of network connectivity, provide audit capabilities, and offer services through software or applications. However, this did not significantly affect the decision to use the service at the 0.05 level.